Problems and prospects of the temple architecture of Altai (Проблемы и перспективы храмового зодчества на Алтае) - Yuri Alexandrovich Kreydun (Культурное наследие Сибири, 2019)
The article deals with the process of revival of building of Orthodox temples by example of newly built churches in Altai Region and Altai Republic. Architectural analysis of church buildings revealed the most characteristic features of church buildings. Specifies the facts that some considerable traditions are lost both from technological and architectural forms of temple buildings in the region were not yet available, targeted programmes and a shortage of experienced engineers and skilled craftsmen in the field of temple architecture and religious art (Исследуется процесс возрождающегося православного храмоздательства на примере храмов Алтайского края и Республики Алтай. В результате архитектурно-исторического анализа выявлены наиболее характерные черты церковных зданий. Указывается на значительную утрату традиций с точки зрения как технологии, так и архитектурных форм храмовых зданий, поскольку в регионе пока отсутствуют целевые программы, наблюдается недостаток опытных проектировщиков и квалифицированных мастеров в сфере храмового зодчества и церковного искусства.).